Heterozygote Wdr36-deficient mice do not develop glaucoma - Gallenberger, Martin; Kroeber, Markus; Maerz, Loreen; Koch, Marcus; Fuchshofer, Rudolf; Braunger, Barbara M.; Iwata, Takeshi; Tamm, Ernst R. (Experimental Eye Research, 2014)
There is an ongoing controversy regarding the role of WDR36 sequence variants in the pathogenesis of primary open-angle glaucoma (POAG). WDR36 is a nucleolar protein involved in the maturation of 18S rRNA. The function of WDR36 is essential as homozygous Wdr36-deficient mouse embryos die before reaching the blastocyst stage. Here we provide a detailed analysis of the phenotype of heterozygous Wdr36-deficient mice. Loss of one Wdr36 allele causes a substantial reduction in the expression of Wdr36 mRNA. In the eyes of Wdr36+/- animals, the structure of the tissues involved in aqueous humor circulation and of the optic nerve head are not different from that of control littermates. In addition, one-year-old Wdr36+/- animals do not differ from wild-type animals with regards to intraocular pressure and number of optic nerve axons. The susceptibility of retinal ganglion cells to excitotoxic damage induced by NMDA is similar in Wdr36+/- and wild-type animals. Moreover, the amount of optic nerve axonal damage induced by high IOP is not different between Wdr36+/- and wild-type mice. Transgenic overexpression of mutated Del605-607 Wdr36 in Wdr36+/- animals does not cause changes in the number of optic nerve axons or susceptibility to excitotoxic damage. In addition, analysis of 18S rRNA maturation in Del605-607 Wdr36+/- or Wdr36+/- mice does not show obvious differences in rRNA processing or in the amounts of precursor forms when compared to wild-type animals. Our data obtained in Wdr36+/- mice do not support the assumption of a causative role for WDR36 in the pathogenesis of POAG.
CRIS-Team Scopus Importer:2023-04-11
Keywords: Animal model; Genetics; Primary open-angle glaucoma